2021
DOI: 10.1038/s41588-021-00895-y
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-resolved genome assembly provides insights into evolutionary history of the tea plant Camellia sinensis

Abstract: Tea is an important global beverage crop and is largely clonally propagated. Despite previous studies on the species, its genetic and evolutionary history deserves further research. Here, we present a haplotype-resolved assembly of an Oolong tea cultivar, Tieguanyin. Analysis of allele-specific expression suggests a potential mechanism in response to mutation load during long-term clonal propagation. Population genomic analysis using 190 Camellia accessions uncovered independent evolutionary histories and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 213 publications
(181 citation statements)
references
References 69 publications
8
153
0
Order By: Relevance
“…Only one transcript switched the expressed allele between leaf and stem tissues. This is also similar to the patterns observed in ginger and tea plant [43,44]. We previously reported more genes with ASE for cassava 60444 and TME3 [8] because different RNA isoforms (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Only one transcript switched the expressed allele between leaf and stem tissues. This is also similar to the patterns observed in ginger and tea plant [43,44]. We previously reported more genes with ASE for cassava 60444 and TME3 [8] because different RNA isoforms (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…The clean reads were uniquely aligned to the latest reference genome (cv. Tieguanyin) (Zhang et al, 2021) using HISAT2.2.4 (Anders et al, 2015 with the default parameters. The expression abundance and variations were estimated in fragments per kilobase of transcript per million fragments mapped (FPKM).…”
Section: High-throughput Rna-seqmentioning
confidence: 99%
“…We examined the diversity characteristics in some perennial tree species (Additional file 4: Table S3) and found that unlike common annual crops with dramatic reduction of genetic diversity during crop domestication and improvement, the genetic diversity of domesticated or improved perennial trees is not necessarily lower than their progenitors. For example, in the tea tree population studies [19,20], the nucleotide diversity of cultivated tea plants is higher than their wild ancestors. In European pears, although the θ w of wild population is much higher than domesticated one, the θ π value, on the contrary, is slightly higher in the domesticated population [16] (Additional file 4: Table S3).…”
Section: Genetic Diversity Of Different Walnut Populationsmentioning
confidence: 99%